Piquasso: A Photonic Quantum Computer Simulation Software Platform - Zoltán Kolarovszki; Tomasz Rybotycki; Péter Rakyta; Ágoston Kaposi; Boldizsár Poór; Szabolcs Jóczik; Dániel T. R. Nagy; Henrik Varga; Kareem H. El-Safty; Gregory Morse; Michał Oszmaniec; Tamás Kozsik; et al. (Quantum)
We introduce the Piquasso quantum programming framework, a full-stack open-source software platform for the simulation and programming of photonic quantum computers. Piquasso can be programmed via a high-level Python programming interface enabling users to perform efficient quantum computing with discrete and continuous variables. Via optional high-performance C++ backends, Piquasso provides state-of-the-art performance in the simulation of photonic quantum computers. The Piquasso framework is supported by an intuitive web-based graphical user interface where the users can design quantum circuits, run computations, and visualize the results.